2021
DOI: 10.3389/fonc.2021.650603
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting Effects of Calebin A on Malignancy of CRC Cells in Multicellular Tumor Microenvironment

Abstract: BackgroundTumor microenvironment (TME) provides the essential prerequisite niche for promoting cancer progression and metastasis. Calebin A, a component of Curcuma longa, has long been investigated as a safe multitargeted agent with antitumor and anti-inflammatory properties. However, the multicellular-TME-induced malignancy and the antitumorigenic potential of Calebin A on colorectal cancer (CRC) cells in 3D-alginate cultures are not yet understood, and more in-depth research is needed.Methods3D-alginate tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
3
12
0
Order By: Relevance
“…Therefore, to obtain more information about the underlying mechanism, we screened for NF-kB signaling in this work and found that p65-NF-kB, FAK (downstream of β1-integrin), and cyclin D1 (protein regulating cell cycle progression), strongly and at the same time, caspase-3 (apoptosis) was poorly expressed in TME. In numerous previous publications by our group, we compared the expression of these proteins in the TME of the cell lines also used in this work with a basal control without TME, confirming the notion that the described protein expressions are significantly induced in the TME [30,46,[48][49][50]. In parallel, blocking the β1-integrin receptor by the antibody against β1-integrin but not against other integrin chains, the β5-integrin antibody, or by treatment with the integrin epitope suppressor RGD, but not with RGE peptides, led to inhibition of resveratrol-depressed p65-NF-kB, p-FAK, and cyclin D1 expression, and resveratrolactivated caspase-3.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, to obtain more information about the underlying mechanism, we screened for NF-kB signaling in this work and found that p65-NF-kB, FAK (downstream of β1-integrin), and cyclin D1 (protein regulating cell cycle progression), strongly and at the same time, caspase-3 (apoptosis) was poorly expressed in TME. In numerous previous publications by our group, we compared the expression of these proteins in the TME of the cell lines also used in this work with a basal control without TME, confirming the notion that the described protein expressions are significantly induced in the TME [30,46,[48][49][50]. In parallel, blocking the β1-integrin receptor by the antibody against β1-integrin but not against other integrin chains, the β5-integrin antibody, or by treatment with the integrin epitope suppressor RGD, but not with RGE peptides, led to inhibition of resveratrol-depressed p65-NF-kB, p-FAK, and cyclin D1 expression, and resveratrolactivated caspase-3.…”
Section: Discussionsupporting
confidence: 84%
“…Previous reports have indicated CBA’s apoptotic, anti-cell proliferation, and anti-inflammatory properties in colorectal cancer cells. 9 Other reports have shown that CBA has a robust antiproliferative effect on NF-kB-mediated cell proliferation in three colorectal cancer cells (HCT-116, RKO, and SW480). 10 Mechanistically, CBA was reported to suppress NF-kB induced by various stimuli in different cell lines by suppressing the direct binding of the NF-κB/p65 subunit essential for NF-kB transactivation and binding to DNA.…”
Section: Discussionmentioning
confidence: 94%
“… 8 It has also been reported to ameliorate obesity or high-fat diet-induced colitis. 9 HPSB has antiproliferative effects on multidrug-resistant human leukemic HL60 and K562 cells. 10 Other studies have also shown that topical treatment with HPSB prevents mouse skin tumorigenesis.…”
Section: Introductionmentioning
confidence: 95%
“…The dissolved CRC cells were washed off with Hank's salt solution, wells were replenished with the 3% FBS Frontiers in Pharmacology frontiersin.org cell culture medium, and wound incisions were photographed using a phase contrast Axiovert 40 CFL microscope (Zeiss, Oberkochen, Germany). Now, the trial substances were added for 2 h, and then, the glass plates were located in a 3D-model, as already used previously (Buhrmann et al, 2021b). The 3D-environment was built in 6-well plates with each well containing a small steel bridge on which the CRC-glass plates were placed.…”
Section: Migration Investigationmentioning
confidence: 99%